Predicting Religious Undergraduates' Career Development: The Salient Roles of Religious Calling, Life Satisfaction, and Quest Religiosity - Puffer, Keith A. (Religions, 2023)
Americans, over several decades, have consistently identified themselves as being religious and/or spiritual. Even though religious devotion has been recognized as a relevant diversity facet, therapeutic applications have been problematic. In the career development literature, numerous studies examined the influence of religion/spirituality (R/S) and generally categorized them in three ways. These include R/S as religious calling, as an integral feature of career interests and values, and as a supportive role. Yet, notable gaps exist among the articles. Researchers tended to operationalize R/S in a unidimensional manner, as a stand-alone construct instead of comprising multiple features. Investigations of religious calling in vocational matters were not recent. Further, few authors considered the influence of quest religious orientation on career development. In the present study, the relationships between seven career development and thirteen R/S variables using a sample of religious undergraduates (n = 290) enrolled in a career exploration course at a Christian university in the Midwest region of the United States were investigated. Findings from hierarchical regression analyses of vocational identity, career commitment, and career indecision checking for gender effects revealed three consistent salient predictors – religious calling, life-satisfaction, and quest religiosity. Implications of the results and possible therapeutic applications for career counselors are proposed.